Antioxidant Activity Analysis Using DPPH and Total Phenol Methods of Soursop Leaf Extract (Annona muricata L.) - Dwi Kartika Wati; Kammal Nizam Amrullah; Salsabilatul Mukarommah; Nour Athiroh Abdoes Sjakoer; Faisal Faisal; Majida Ramadhan; Nafisa Nafisa (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
Soursop leaves (Annona muricata L.) are known to contain various bioactive compounds with potential antioxidant properties. This study aimed to evaluate the antioxidant activity of soursop leaf extract using the DPPH (2,2-diphenyl-1-picrylhydrazyl) method and to determine its total phenolic content using the Folin–Ciocalteu method. Antioxidant activity was assessed at extract concentrations of 500 and 1000 ppm, with quercetin used as a positive control. The results showed that the soursop leaf extract exhibited very strong antioxidant activity, with an IC50 value of 9,486 ppm. The total phenolic content of the extract was relatively high, ranging from 102,929 to 195,702 mg GAE/g extract. The strong antioxidant activity observed is likely associated with the high content of phenolic compounds, which play a crucial role in scavenging free radicals. These findings suggest that soursop leaf extract has significant potential as a natural antioxidant source for applications in the functional food and pharmaceutical industries.